Bone methabolic disorders in HIV positive patients: a case report. : The importance of drug therapy in preventing decrease of bone mineral density in HIV and HCV positive patients - De Carli, Angelo; Gaj, Edoardo; Desideri, Davide; Scrivano, Marco; fedeli, gianluca; Vadala, Antonio Pasquale (Acta Biomedica Atenei Parmensis, 2020)
Fractures in patients affected by HIV are more frequent than what is reported in patients with no retroviral diseases. Chronic infection with HIV likely contributes to increased systemic inflammation, which has been associated with increased rates of fracture. We report a case of a 56-year-old male (HIV + in treatment with Atripla) heavy worker, at the beginning affected by intra-articular proximal humerus fracture treated with endoprosthesis replacement and later by periprosthetic fracture treated with plate, screws and cerclages. Follow up was performed with clinical evaluation (ROM, VAS, Quick Dash, ASES, Simple shoulder test, UCLA Score, Constant score) and shoulder radiographs. Bone metabolism disorders in HIV patients lead to low BMD values, changes in bone turnover markers, and histomorphometric abnormalities, especially when HIV is present along with HCV or other hepatopathies. Additional therapy with bisphosphonate and Vitamin D should always be carried out when possible to prevent such types of orthopaedic complications.